Combined fiber probe for fluorescence lifetime and Raman spectroscopy - Dochow, Sebastian; Ma, Dinglong; Latka, Ines; Bocklitz, Thomas; Hartl, Brad; Bec, Julien; Fatakdawala, Hussain; Marple, Eric; Urmey, Kirk; Wachsmann-Hogiu, Sebastian; Schmitt, Michael; Marcu, Laura; et al. (Analytical and Bioanalytical Chemistry, 2015)
In this contribution we present a dual modality fiber optic probe combining fluorescence lifetime imaging (FLIm) and Raman spectroscopy for in vivo endoscopic applications. The presented multi-spectroscopy probe enables efficient excitation and collection of fluorescence lifetime signals for FLIm in the UV/visible wavelength region, as well as of Raman spectra in the near-IR for simultaneous Raman/FLIm imaging. The probe was characterized in terms of its lateral resolution and distance dependency of the Raman and FLIm signals. In addition, the feasibility of the probe for in vivo FLIm and Raman spectral characterization of tissue was demonstrated. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-04-20
Keywords: Bimodal; Fiber probes; Fluorescence lifetime; Imaging; Raman spectroscopy